Pengaruh Faktor-Faktor Penerapan Balanced Scorecard Terhadap Kinerja Perusahaan (Studi Pada Dealer Honda di Surakarta) - Sihab, Syavira Imaniar (Journal of Economics Business Finance and Accounting, 2023)
This study aims to determine and analyze the influence of: 1) financial perspective on company performance, 2) customer perspective on company performance, 3) internal business perspective on company performance, 4) learning and growth on company performance, and 5) financial perspective, customer perspective, business perspective and internal learning and growth on company performance Honda Dealer, Surakarta. This research is quantitative research. The population of this study were all employees and customers of Honda Dealer, Surakarta with a sample of 120 respondents. Data collection techniques using a questionnaire. The analysis technique used is multiple linear regression analysis. The results of this study indicate: 1) Financial Perspective has an effect on Company Performance of 0.202 with a tcount of 2.102. and a significance of 0.038; 2) Customer Perspective has an effect on Company Performance of 0.351 with a tcount of 2,919 and a significance of 0.004; 3) The Internal Business Perspective has an effect on the Company's performance of 0.216 with a tcount of 2.189 and a significance of 0.031; 4) Learning and Growth Perspective has an effect on Company Performance of 0.452 with a tcount of 4.061 and a significance of 0.000; 5) Financial perspective, customer perspective, internal business perspective, and learning and growth perspective affect the company's performance with an Fcount of 62,356 and a significance value of 0.000. The conclusion of this research is the financial perspective, customer perspective, internal business perspective, and learning and growth perspective affect the company's performance either partially or simultaneously.